1993
DOI: 10.1002/bjs.1800801135
|View full text |Cite
|
Sign up to set email alerts
|

Lymph node metastases in early rectal cancer

Abstract: Local excision of early rectal tumours is an attractive proposition, avoiding the morbidity and mortality of major resection and possible permanent stoma. This study was designed to investigate the incidence of lymph node metastases associated with tumours that are locally confined to the bowel wall. A total of 454 rectal excision specimens were reviewed. Twenty-two (20 per cent) of 109 patients with tumours locally confined to the bowel wall had metastases in local lymph nodes, although 14 of these had only o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
3
2

Year Published

1997
1997
2008
2008

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(29 citation statements)
references
References 14 publications
1
23
3
2
Order By: Relevance
“…29 The lack of distinction between the 2 by some authors and nonuniform criteria for grading rectal adenocarcinomas have produced high rates of interobserver and intraobserver variation and variable results for the significance of adenocarcinoma grade. 21 highest grade only along the advancing edge of the adenocarcinoma 22 ; or the amount of microacinar structures or undifferentiated areas. 2845 One major surgical pathology textbook has recommended that adenocarcinomas be graded based on an overview of the glandular architecture, but it mentions nothing about the morphologic features of the advancing edge of the adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…29 The lack of distinction between the 2 by some authors and nonuniform criteria for grading rectal adenocarcinomas have produced high rates of interobserver and intraobserver variation and variable results for the significance of adenocarcinoma grade. 21 highest grade only along the advancing edge of the adenocarcinoma 22 ; or the amount of microacinar structures or undifferentiated areas. 2845 One major surgical pathology textbook has recommended that adenocarcinomas be graded based on an overview of the glandular architecture, but it mentions nothing about the morphologic features of the advancing edge of the adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Including the results of our study, LN metastases occur in 3% to 15% of specimens with adenocarcinomas confined to the submucosa of the bowel wall. [22][23][24][25][26] Given this low rate of LN metastasis, local excision of minimally invasive rectal adenocarcinomas would seem to be the procedure of choice compared with an abdominoperineal resection. The major drawback of local excision is the inability to assess the status of perirectal LNs.…”
Section: Discussionmentioning
confidence: 99%
“…Pathologists may base overall tumor grade on a qualitative impression of the sum of global histologic features or on the highest grade features seen anywhere in the neoplasm (whatever their extent; ref. 102), relative proportion of undifferentiated tumor (103,104), or degree of differentiation along the advancing edge of the tumor (105).…”
Section: Tumor Gradementioning
confidence: 99%
“…1,2 However, it was recently reported that some T1 carcinomas can be treated by a local resection without either a nodal dissection or endoscopic surgery, which seems justified only for carcinomas without lymph node metastasis. 3,4 Therefore, the prediction of the nodal status in patients with T1 carcinomas is important in the preoperative selection of treatment.…”
mentioning
confidence: 99%